Managing coastal areas, managing conflicts: an essay on Icapui - Lustosa, Paulo Henrique; Maia, Saulo Robério Rodrigues; Albuquerque, Bruna Maria Rodrigues de Freitas; Melo, Herbart dos Santos (Revista Hipótese, 2017)
The municipality of Icapui is one of the most sensitive areas of the State on this ussue, thus, the present essay looks toward this region as a reference for an interdisciplinary approach considered necessary to overcome this challenges, analyzing its socioeconomic indicators, the interests in conflict, its impacts on the coastal ecosystem and suggests alternatives for a sustainable management of the territory.